Structure and properties of a boronized crankshaft coating - Hazar, Hanbey; Tansu, Mahmut Nedim (Carl Hanser Verlag, 2020)
In this study, the boronizing method was applied to a crankshaft of a diesel engine, and exposed to bending and torsional stress and pressure, and the material characterization was examined. The boronizing method was applied to the crankshaft at 950 degrees C for 4 hours. Optical microscope, microhardness, SEM, EDAX, XRD, wear, TGA and corrosion analyses were performed to determine the material characterization. According to the results obtained, the optical and SEM images showed the presence of FeB and Fe2B layers, and EDAX and XRD analyses showed the presence of boron and its compounds. A 6.7-fold increase in hardness was observed in the microhardness analysis and 4-fold wear resistance was observed in the wear analysis. Resistance of 85 % was observed in the corrosion analysis and oxidation delay of 300 degrees C were observed in the TGA test. After wear analysis, SEM and XRD analyses were performed and the surfaces were examined.
Keywords: Boronizing; wear; microhardness; corrosion; oxidation